High replacement of soybean meal by different types of rapeseed meal is detrimental to rainbow trout (Oncorhynchus mykiss) growth, antioxidant capacity, non-specific immunity and Aeromonas hydrophila tolerance - Jiang, Wen; Wang, Hengzhi; Zhang, Lu; Mi, Haifeng; Deng, Junming (Frontiers in Nutrition, 2024)
A 12-week feeding trial was conducted to evaluate the effects of replacing soybean meal with different types of rapeseed meal (RSM; Chinese 95-type (oil press model) rapeseed meal [C95RM], Chinese 200-type rapeseed meal [C200RM], cold pressed rapeseed cake [CPRC], Indian rapeseed meal [IRM] and Canadian rapeseed meal [CRM]) on growth, antioxidant capacity, non-specific immunity and Aeromonas hydrophila infection tolerance in 990 fingering (average weight 12.77 ± 0.01g) rainbow trout (Oncorhynchus mykiss). A basal diet was prepared using fishmeal and soybean meal as the main protein sources, the other ten diets were formulated with five types of RSM at 20% (C95RM20, C200RM20, CPRC20, IRM20, CRM20) or 35% (C95RM35, C200RM35, CPRC35, IRM35, CRM35) inclusion levels to replace iso-nitrogenous soybean meal. Regardless of the RSM source, dietary inclusion of 20% RSM significantly reduced the weight gain rate (WGR) and digestive enzymes activities (except C200RM20) of fish, but increased the blood urea nitrogen (BUN) and hepatic malondialdehyde (MDA) content (except CRM20). Fish fed with CPRC20 and IRM20 exhibited relatively higher plasma cortisol and MDA content, but lower content/activities of triiodothyronine (T3), thyroxine (T4) and glutathione peroxidase (GPx) in plasma, lysozyme (LZM) and complement 3 (C3) in serum, catalase (CAT) in liver, and respiratory burst activity (RBA) of head kidney macrophages. The intestinal and hepatic tissues fed with 20% RSM were damaged to some extent, with the CPRC20 and IRM20 groups being the most severely affected. Regardless of the RSM source, dietary inclusion of 35% RSM significantly decreased WGR and digestive enzymes activities, but significantly increased plasma BUN and MDA content. The fish fed with CPRC35 and IRM35 exhibited relatively higher plasma cortisol, MDA, serum triglyceride, BUN content, but lower content/activities of T3, T4, C3 and LZM in serum, CAT, peroxidase and GPx in plasma, CAT in liver, RBA and phagocytic activity of head kidney macrophage. The hepatic and intestinal tissues damage was the worst in the IRM35 group among the 35% RSM inclusion groups. These results indicate that including ≥ 20% RSM in the diet, regardless of the source, reduced the growth, antioxidant capacity, immunity, and survival to Aeromonas hydrophila infection in rainbow trout.